2014
DOI: 10.4067/s0716-10182014000600015
|View full text |Cite
|
Sign up to set email alerts
|

Características clínicas, factores de riesgo y perfil de susceptibilidad de las infecciones por micobacterias documentadas por cultivo, en un hospital universitario de alta complejidad en Medellín (Colombia)

Abstract: In our study immune suppression is the main risk factor for extrapulmonary and disseminated disease. Resistance, MDR and XDR is higher in inpatients with TB. MNT infections are not uncommon in our country.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 11 publications
0
1
0
2
Order By: Relevance
“…A Colombian research conducted from 2004 to 2011 in a tertiary hospital reported that among people with a positive mycobacterial culture, most people were immunosuppressed (HIV, chronic use of steroids or immunosuppressants, chronic kidney disease, diabetes mellitus, etc.). The frequency of NTM was 9.1% [ 73 ]. In the prisons where the participants were incarcerated, there were no reports of NTM in our group’s previous study of tuberculosis disease [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…A Colombian research conducted from 2004 to 2011 in a tertiary hospital reported that among people with a positive mycobacterial culture, most people were immunosuppressed (HIV, chronic use of steroids or immunosuppressants, chronic kidney disease, diabetes mellitus, etc.). The frequency of NTM was 9.1% [ 73 ]. In the prisons where the participants were incarcerated, there were no reports of NTM in our group’s previous study of tuberculosis disease [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Esta distribución coincidió con lo que se ha informado para este tipo de población: de acuerdo con la OMS, en el 2014 se presentó un aumento de 43,9 % en los casos de tuberculosis asociada con la infección por HIV con respecto al año anterior (2), asociación que es la más frecuente en el caso de la tuberculosis extrapulmonar, como se ha evidenciado en varios estudios locales en instituciones de alta complejidad, en los cuales se registraron diferencias significativas con respecto a los pacientes inmunocompetentes (25). Por ello, el médico siempre debe sospechar su presencia; se sabe que en los pacientes con infección por HIV se debe buscar tuberculosis, y viceversa (26).…”
Section: Discussionunclassified
“…Es de resaltar que su incidencia se ha mantenido relativamente constante en los últimos años; mientras que la de la TB pulmonar ha venido en descenso. En parte, se cree que es debido a la mayor frecuencia de infección por VIH (la coinfección con TB es cercana al 9 %) (10,11), al uso creciente de quimioterapéuticos o agentes biológicos, patrones de migración y también al desarrollo de las herramientas diagnósticas (12,13).…”
Section: Epidemiología Y Factores De Riesgounclassified